Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1371/journal.pone.0068609
|View full text |Cite
|
Sign up to set email alerts
|

Altered Resting State Brain Dynamics in Temporal Lobe Epilepsy Can Be Observed in Spectral Power, Functional Connectivity and Graph Theory Metrics

Abstract: Despite a wealth of EEG epilepsy data that accumulated for over half a century, our ability to understand brain dynamics associated with epilepsy remains limited. Using EEG data from 15 controls and 9 left temporal lobe epilepsy (LTLE) patients, in this study we characterize how the dynamics of the healthy brain differ from the “dynamically balanced” state of the brain of epilepsy patients treated with anti-epileptic drugs in the context of resting state. We show that such differences can be observed in band p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
68
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 89 publications
14
68
1
Order By: Relevance
“…Previous studies have suggested the use of graph metrics in clinical trials (Petrella, 2011) and as diagnostic tools (Quraan et al, 2013;Schoonheim et al, 2013). There is clear appeal to this approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested the use of graph metrics in clinical trials (Petrella, 2011) and as diagnostic tools (Quraan et al, 2013;Schoonheim et al, 2013). There is clear appeal to this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated significant differences in metrics derived from graphs of brain networks between diseased and healthy groups as well as in normal development (Supekar et al, 2009), for example, in multiple sclerosis (He et al, 2009), Alzheimer's (Buckner et al, 2009;Stam et al, 2009), Parkinson's (Göttlich et al, 2013), epilepsy (Quraan et al, 2013), and body dysmorphic disorder (Arienzo et al, 2013) [for reviews see Bassett and Bullmore (2009);Menon (2011);Wang et al (2010)], and have offered various interpretations of these findings. With this wave of positive results, some authors have suggested the use of graph metrics as surrogate markers in clinical trials (Petrella, 2011) and even suggested that they have potential as diagnostic tools (Quraan et al, 2013;Schoonheim et al, 2013). However, such applications Sir Peter Mansfield Imaging Centre, University of Nottingham, Nottingham, United Kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that asymmetric and slow activity of the delta band (1-4 Hz) can reliably lateralize to the epileptogenic hemisphere [14,[60][61][62]. Indeed, significant differences in delta band activity were found between TLE patients and controls in network analyses [31,63,64]. Thus, we only selected one frequency band, the delta band, as our frequency band of interest.…”
Section: Complexitymentioning
confidence: 99%
“…Widespread PSD differences between patients with epilepsy and controls have been already described. 37,38 They are possibly related to the medications [39][40][41] or to the disease itself. An increase of power can be produced by a larger number of neurons oscillating synchronously, higher synchrony or both.…”
Section: Other Frequency Bands During Sleepmentioning
confidence: 99%